ASPEK HUKUM PERJANJIAN WARALABA (FRANCHISE) DALAM PERSPEKTIF HUKUM PERDATA DAN HUKUM ISLAM - Idrus, Norman Syahdar (Jurnal Yuridis, 2017)
Trade in Indonesia currently dominated by trade in goods and services which is a collaboration between Indonesia businessmen and foreign businessmen, or between Indonesia businessmen and Indonesian businessmen.Initially the franchise is a business concept concerning the granting of intellectual property rights and operational system by the franchisor to the franchisee which then becomes the legal institution that regulates a legal relationship between the franchisor and the franshisee set forth in a franchise agreement as first set in Act number 9 of 1995 concerning Small Business. The focus of this study intends to discuss franchise agreements in the perspective of civil law and Islamic law that aimesto achieve benefit for mankind.